Air Pollution Is Associated With Ischemic Stroke via Cardiogenic Embolism. Issue 1 (January 2017) - Chung, Jong-Won; Bang, Oh Young; Ahn, Kangmo; Park, Sang-Soon; Park, Tai Hwan; Kim, Jae Guk; Ko, Youngchai; Lee, SooJoo; Lee, Kyung Bok; Lee, Jun; Kang, Kyusik; Park, Jong-Moo; et al.
Abstract : Background and Purpose—: The aim of the study was to assessed the impact of short-term exposure to air pollution on ischemic stroke subtype, while focusing on stroke caused via cardioembolism. Methods—: From a nationwide, multicenter, prospective, stroke registry database, 13 535 patients with acute ischemic stroke hospitalized to 12 participating centers were enrolled in this study. Data on the hourly concentrations of particulate matter <10 μm, nitrogen dioxide (NO2 ), sulfur dioxide (SO2 ), ozone (O3 ), and carbon monoxide (CO) were collected from 181 nationwide air pollution surveillance stations. The average values of these air pollutants over the 7 days before stroke onset from nearest air quality monitoring station in each patient were used to determine association with stroke subtype. The primary outcome was stroke subtype, including large artery atherosclerosis, small-vessel occlusion, cardioembolism, and stroke of other or undetermined cause. Results—: Particulate matter <10 μm and SO2 concentrations were independently associated with an increased risk of cardioembolic stroke, as compared with large artery atherosclerosis and noncardioembolic stroke. In stratified analyses, the proportion of cases of cardioembolic stroke was positively correlated with the particulate matter <10 μm, NO2, and SO2 quintiles. Moreover, seasonal and geographic factors were related to an increased proportion of cardioembolic stroke, which may be attributed to the high levels of air pollution. Conclusions—: Our findings suggest that the short-term exposure to air pollutants is associated with cardioembolic stroke, and greater care should be taken for those susceptible to cerebral embolism during peak pollution periods. Public and environmental health policies to reduce air pollution could help slow down global increasing trends of cardioembolic stroke. Abstract : Supplemental Digital Content is available in the text.